DEVELOPMENT OF THE INFORMATION SYSTEM ARCHITECTURE FOR THE IMPLEMENTATION OF AN INTEGRATED INFORMATION TECHNOLOGY FOR CALCULATING THE HEALTH STATUS OF AN IT PROJECT PORTFOLIO - Lanskykh, Yevhen; Pomohaibo, Dmytro (Sworld-Us Conference proceedings, 2025)
In the context of high market uncertainty, traditional project management approaches are losing effectiveness. In response, the authors previously developed an integrated method for calculating the Health Status (HS), which synthesizes operational, techn